2012
DOI: 10.1158/1535-7163.mct-12-0193
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitor of Histone Deacetylases Sodium Butyrate Enhances the Cytotoxicity of Mitomycin C

Abstract: The use of histone deacetylase inhibitors has been proposed as a promising approach to increase the cell killing effect of DNA damage-inducing drugs in chemotherapy. However, the molecular mechanism of their action remains understudied. In the present article, we have assessed the effect of the histone deacetylase inhibitor sodium butyrate on the DNA damage response induced by the crosslinking agent mitomycin C. Sodium butyrate increased mitomycin C cytotoxicity, but did not impair the repair pathways required… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…Butyrate has been shown to abrogate the S-phase cell cycle checkpoint, and exhibits colon cancer preventive effects through cell proliferation regulation [ 5 , 6 , 28 , 29 , 30 ]. As there are few reports concerning the apoptotic potential, we propose that butyrate plays differential roles in the cell proliferation of noncancerous NCM460 cell and cancerous HCT116 colon cells through cellular signaling modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate has been shown to abrogate the S-phase cell cycle checkpoint, and exhibits colon cancer preventive effects through cell proliferation regulation [ 5 , 6 , 28 , 29 , 30 ]. As there are few reports concerning the apoptotic potential, we propose that butyrate plays differential roles in the cell proliferation of noncancerous NCM460 cell and cancerous HCT116 colon cells through cellular signaling modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium butyrate inhibited histone deacetylase leading to hyperacetylation of these basic proteins and loosening of their attachment to DNA. This allowed increased transcription of genes and caused apoptosis in cancer cells (Gospodinov et al, 2012, Luhrs et al, 2002, Smith et al, 1998. In cultured fibroblasts, sodium butyrate treatment increased methylation of DNA (Boffa et al, 1994).…”
Section: Acetylation Of Histones Phosphorylation Of Proteins and Methylation Of Dna By Sodium Butyratementioning
confidence: 99%
“…For example, other investigators have reported that SAHA mediated the production of reactive oxygen species SAHA that contributed to cell death [46;47]. We hypothesized that, if the mechanism of synergy was due primarily to the SAHA-mediated inhibition of HR, then SAHA would synergistically enhance GCV cytotoxicity in the HR-proficient but not in the HR-deficient CHO cells.…”
Section: Discussionmentioning
confidence: 93%